An assessment of the e-learning readiness of faculty and undergraduate students of the Institute of Library and Information Science - Nogoy, Lemuel Ramon M. (2007)
E-learning is the convergence of internet technology, computer technology and learning. E-learning has shown its versatility having been implemented by organizations in various disciplines and having been used in numerous countries. It shifts the focus from the instructor to the student. Organizations and their members will enjoy a host of benefits by embracing e-learning. However, they must perform careful planning and they must address areas of concern to realize its full potential. In line with this, this study determined the readiness of the faculty and undergraduate students of the UP Institute of Library and Information Science for e-learning. The study gauged the respondents' readiness in terms of their attitudes and perceptions with regard to e-learning, their computer skills as well as the technology infrastructure available to them.